2020
DOI: 10.1021/acs.oprd.9b00410
|View full text |Cite
|
Sign up to set email alerts
|

Carbon as a Simple Support for Redox Biocatalysis in Continuous Flow

Abstract: A continuous packed bed reactor for NADH-dependent biocatalysis using enzymes co-immobilized on a simple carbon support was optimized to 100% conversion in a residence time of 30 min. Conversion of pyruvate to lactate was achieved by co-immobilized lactate dehydrogenase and formate dehydrogenase, providing in situ cofactor recycling. Other metrics were also considered as optimization targets, such as low E factors between 2.5–11 and space-time yields of up to 22.9 g L –1 h –1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Similar results were observed by Poznansky et al for the NADH-dependent bio catalytic conversion of pyruvate to lactate. In this case, the STY was 5.52 g L –1 d –1 for the batch process, while in the flow process, a STY of 269 g L –1 d –1 was reported, thus demonstrating that higher productivity can be achieved using the continuous-flow reactor …”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Similar results were observed by Poznansky et al for the NADH-dependent bio catalytic conversion of pyruvate to lactate. In this case, the STY was 5.52 g L –1 d –1 for the batch process, while in the flow process, a STY of 269 g L –1 d –1 was reported, thus demonstrating that higher productivity can be achieved using the continuous-flow reactor …”
Section: Resultsmentioning
confidence: 73%
“…In this case, the STY was 5.52 g L −1 d −1 for the batch process, while in the flow process, a STY of 269 g L −1 d −1 was reported, thus demonstrating that higher productivity can be achieved using the continuous-flow reactor. 33 Comparative Evaluation of Alternative Immobilization Systems. For the purpose of benchmarking, different immobilization platforms, namely, CLEA (cross-linked enzyme aggregates) epoxy support, ECR8285, (Purolite, U.K.) were compared on the immobilization efficiency on apKRED-9 along with amino support LX1000HA and CEP platform.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A recent study demonstrated DoE as an effective method for optimizing multienzyme biocatalytic flow reactions, yet avoided optimization of the enzyme loadings despite a suggestion that this would offer further improvements. 37 Evidently, optimizing enzyme ratios is not a trivial problem when using immobilized enzymes in flow, even when applying DoE to reduce the necessary experimentation. Others attempt to tackle this challenge through the selection of the best ratio from a few arbitrary trials 38 or simply do not optimize enzyme ratios.…”
Section: ■ Introductionmentioning
confidence: 99%
“…First, the catalysts SH/C and SH + Hyd1/C were tested in H 2driven NADH-generating assays to determine the batch catalyst performance for the NADH generation step, Figure 3A. The enzymes were immobilized on carbon black (Black Pearls 2000, BP2000, ∼10 nm), which we have previously found to be a versatile enzyme support, according to the immobilization protocol described in General Enzyme Immobilization Procedure for Batch Studies (Poznansky et al, 2020). The enzyme-modified carbon particles were transferred into 800 μl of H 2 -saturated NAD + (0.1 mM) in Tris-HCl (100 mM, pH 8.0) in a cuvette, then the reaction was monitored in situ by UV-Vis.…”
Section: Heterogeneous Biocatalysts For H 2 -Driven Nadh Recycling In Batch Reactionsmentioning
confidence: 99%